Recommendations for improvement based on fire incident case at Lot no. 4.18b (Relysis Computer), Level 4, Plaza Pelangi, Taman Pelangi, Johor Bahru, Johor / Muhammad Akmal Sugeng Triwahyono - Sugeng Triwahyono, Muhammad Akmal (Universiti Teknologi MARA UiTM,Perak, 2022)
The Industrial Training is compulsory for all students of Building Surveying (AP229) for completion of their degree. The purpose of this training is to provide exposure and experience to the students on the real situation of working environment and as an early preparation before the students entering the working world. For the October 2021 – February 2022 session, the training starts on 11 October 2021 until 30 January 2022.This report is the outcome of a whole semester of industrial training period under PNB Commercial Sdn. Berhad, located at Bangunan Pelangi, 1, Jalan Biru, Taman Pelangi, 80400 Johor Bahru, Johor. However, the training session was carried out at one of the company’s client commercial building, Plaza Pelangi, Lot 3.29 & 3.29A, Level, 3, Jalan Kuning, Taman Pelangi, 80400 Johor Bahru, Johor. During the training period, many opportunities were provided to join and learn to be involved in commercial and facilities management matters.